Mapping the black queer geography of Johannesburg’s lesbian women through narrative - Canham, Hugo (PINS-Psychology in Society, 2023)
To be black, working class, living in a township and lesbian is to be a discordant body. This is a markedly different experience than being a socio-economically privileged resident of Johannesburg. This paper sets out to map marginalised sexualities onto existing social fissures emerging out of South Africa’s divided history of apartheid. It argues that while the repeal of the Sexual Offences Act, 1957 (Act No. 23 of 1957, previously the Immorality Act, 1927) and the promulgation of the Civil Union Bill (2006) has had a liberating effect on the lesbian community of Johannesburg; the occupation of physical space is deeply informed by the intersecting confluence of race, class, age, sexuality, and place. Based on the stories of black lesbian women, the paper analyses the occupation of the city’s social spaces to map the differential access to lesbian rights and exposure to prejudice and violence. Findings suggest that their agential movement through space and performances of resistance lends a nuance to the dominant script of victimhood. Their narratives of becoming are shaped by the spaces that they inhabit in both liberating and disempowering ways.